1999
DOI: 10.1007/s002140050475
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study of electrophilic aromatic substitution

Abstract: Proton anities are calculated at all reactive positions for the normal benzenoid hydrocarbons, benzene, naphthalene, phenanthrene and anthracene, a strained benzenoid hydrocarbon, biphenylene, and a nonalternant hydrocarbon,¯uoranthene, and the results are compared to experimental protodetritiation rates. Methods used include PM3 and Hartree-Fock calculations at the STO-3G, 3-21G*, 6-31G* and MP2//6-31G* levels. Generally good agreement is found between theory and experiment with 6-31G* giving the best correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…the protonated regioisomer with the lowest free energy) corresponds to the most probable site for EAS, as was demonstrated by Wang and Streitwieser for several polycyclic aromatic hydrocarbons. 10 This approach is in line with the commonly accepted EAS reaction mechanism when considering the protonated species as a "surrogate" for the arenium ion (Scheme 1). The rationalization of the regioselectivities in the benzene series based on the relative stabilities of the possible sigma complexes is textbook knowledge and Galabov and co-workers 11,12 electrophile have shown that the computed binding energy of the Bromine cation is correlated with the experimentally measured partial rate factors.…”
Section: Introductionsupporting
confidence: 59%
“…the protonated regioisomer with the lowest free energy) corresponds to the most probable site for EAS, as was demonstrated by Wang and Streitwieser for several polycyclic aromatic hydrocarbons. 10 This approach is in line with the commonly accepted EAS reaction mechanism when considering the protonated species as a "surrogate" for the arenium ion (Scheme 1). The rationalization of the regioselectivities in the benzene series based on the relative stabilities of the possible sigma complexes is textbook knowledge and Galabov and co-workers 11,12 electrophile have shown that the computed binding energy of the Bromine cation is correlated with the experimentally measured partial rate factors.…”
Section: Introductionsupporting
confidence: 59%
“…To test the reliability of eq as a proposed definition of Δ – h ( k ), positional selectivity and relative rates (compared to that of benzene) of nitration, benzylation, and chlorination on halobenzenes and alkylbenzenes are studied here. There are a number of earlier attempts where electrophilic substitutions on arenes are studied using reactivity indices based on density functional reactivity theory (DFRT) and other theoretical approaches. ,,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…Nucleus-independent chemical shifts [1] (NICS) show that the induced magnetic field is strongest at the center of the middle ring, which has led some to claim that this ring is the "most aromatic". [2,3] However, it is known that the middle ring of anthracene is the most reactive in reactions such as protonation, [4] Diels-Alder reactions, [5] bromination, and so on. These observations are usually rationalized by considering that the 9,10-addition product (the result of a reaction upon the middle ring) is more aromatic, and thus, more stable, than the 1,4-addition product (resulting from a reaction upon either of the side rings).…”
Section: Introductionmentioning
confidence: 99%